Effects of verbal encouragement on performance of the multistage 20 m shuttle run - Dias Neto, José Marinho; Silva, Fernanda Borges; Oliveira, Artur Luis Bessa de; Couto, Natália Lopes; Dantas, Estélio Henrique Martins; Nascimento, Maria Aparecida de Luca (Acta Scientiarum. Health Sciences, 2015)
Exertion tests for predicting maximal oxygen uptake (VO2) intend to estimate the person maximum performance. Some articles mention the verbal encouragement in their protocol to reach it, while others do not. The objective of the present study is to observe the influence of verbal encouragement every 60 s used by a coach on maximal oxygen uptake, distances covered and final heart rate of adolescents. 12 young male volunteers (aged 16.7±0.45 years) were subjected to a multistage 20 m shuttle run test twice, with a week interval between each test. Half of the sample was given incentives during the first test, and the other half, only in the second test. Significant differences in maximal oxygen uptake (Δ% = 5.14%, p = 0.009), distances covered (Δ% = 9.23%, p = 0.03) and final heart rate (Δ% = 3.21%, p = 0.03) were observed between the two groups, with and without verbal encouragement. The verbal encouragement improved the performance in the test for the three parameters analyzed.